2017
DOI: 10.1016/j.rmcr.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

EGFR or PD-L1 decision for first line therapy in a case series of EGFR positive and PD-L1 >50%

Abstract: Targeted therapies are on the market for the past five years and recently pembrolizumab was approved as first line treatment for patients with PD-L1 >50%. We present three cases of patients which had epidermal growth factor receptor positive expression and programmed death-ligand 1 (PD-L1), PD-L1 >50% overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This observation was attributed to the different patient selection [10] . In the case of a patient with both EGFR mutation and PD-L1 ≥50% tkis are currently advised [11] . Tyrosine kinase inhibitors have few and well controlled adverse effects [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…This observation was attributed to the different patient selection [10] . In the case of a patient with both EGFR mutation and PD-L1 ≥50% tkis are currently advised [11] . Tyrosine kinase inhibitors have few and well controlled adverse effects [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…There are previous studies where regarding EGFR mutations we concluded that "tissue" is the issue, meaning that we might have acquired a sample from the tumor however not a part with PD-L1 expression or ≥50 PD-L1 expression which is the cut off measurement for first line single agent immunotherapy [30]. There are patients which very rarely present two mutations such as, EGFR and PD-L1, even in the case where PD-L1 expression is ≥50 then the patient should be treated with tyrosine kinase inhibitor [31]. Tumor molecular transformation has been also observed where patients without PD-L1 expression after surgery presented PD-L1 expression [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been previously observed that in the mutation for EGFR and KRAS and translocation/fusion for ALK, these genes play a role in the expression of PD-L1 in the case where the tumor expresses both 11. In this case, TKIs should be administered 12. It has been observed that a tumor might transform from adenocarcinoma to small-cell lung cancer (SCLC) or the main lesion might remain the same while metastatic sites might transform and then therapy has to change 13,14.…”
Section: Discussionmentioning
confidence: 99%